Pemikiran Ahl al-Sunnah wa al-Jamaah Perlis - Daud, Zakaria @ Mahmod (Jurnal Usuluddin, 1997)
This articles tries to discuss the views of Ahl al-Sunnah Wa al-Jamaah in Perlis which are looks difference between the views of Ahl al-Sunnah Wa al-Jamaah in the other counties in Malaysia